A Review exploration of Load Balancing Techniques in Cloud Computing - Ms. Roopali Gupta; Dr. Om Prakash Sharma (Educational Administration: Theory and Practice, 2024)
Cloud computing revolutionizes IT services delivery, offering consumers access to virtualized resources over the Internet. As it rapidly replaces in-house infrastructure, various categories of cloud services emerge, creating challenges for consumers in selecting suitable providers. Research highlights disparities between provider criteria and consumer needs, intensifying the difficulty of making informed choices. Categorizations based on access (private vs. public) and services (HaaS, PaaS, SaaS, IaaS) further complicate decision-making. Diverse pricing models exacerbate the challenge, hindering quality and cost comparisons. Cloud computing’s flexibility, enabled by virtual machine migration and economies of scale, attracts businesses seeking superior IT services at reduced costs. The advent of load balancing in cloud computing becomes paramount for optimizing resource usage, enhancing performance, and managing traffic spikes. This paper examines load balancing techniques and their role in addressing challenges and optimizing cloud computing benefits.